PRISON AND ACCESSIBILITY: AN ANALYSIS OF THE SITUATION OF PEOPLE WITH DISABILITIES IN THE BRAZILIAN PRISON SYSTEM - Pereira Spinieli, Andre Luiz [UNESP] (Univ Autonoma Latinoamericana Unaula, 2019)
Based on the premise that persons with disabilities become victims of various institutional violations, especially those of a legal and social nature, when faced with the prison system, the purpose of this document is to reflect on the detention of persons with disabilities in prison, especially for the lack of accessibility, from the perspective of national laws and norms. Based on the objective outlined, the study is delimited by bibliographic research, highlighting Brazilian doctrinal opinions and statistical data regarding the number of persons incarcerated in these conditions. Among the results and conclusions reached, it should be noted that Brazil still has embryonic legal-administrative attitudes regarding the provision of accessibility for the disabled in the prison environment, incompatible with the dignity of these people.
Keywords: Disabled person; prison; accessibility; Brazil